1995
DOI: 10.1177/0013916595273002
|View full text |Cite
|
Sign up to set email alerts
|

General Versus Specific Environmental Concern

Abstract: Using data from a random sample survey of residents In Edmonton, Alberta, and applying LISREL techniques, previously Identified socioeconomic, demographic, and environmental attitudinal predictors are examined and compared across two measures of environmental concem: concem about the environment in general and concem about a specific issue and associated trade-offs. As expected, political party identification and level of education were important determinants in both cases, the significant effect of political … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 22 publications
1
32
0
2
Order By: Relevance
“…Lyons and Breakwell, 1994;Vinning and Ebreo, 1990), is better educated (e.g. Chan, 1999;Wall, 1995), and lives in urban areas (e.g. Samdahl and Robertson, 1989).…”
Section: Socio-demographic Variablesmentioning
confidence: 99%
“…Lyons and Breakwell, 1994;Vinning and Ebreo, 1990), is better educated (e.g. Chan, 1999;Wall, 1995), and lives in urban areas (e.g. Samdahl and Robertson, 1989).…”
Section: Socio-demographic Variablesmentioning
confidence: 99%
“…Education has been shown to be the most consistent predictor for environmental concern (Wall, 1995). Much of the work indicates that individuals with high levels of education tend to care more about the environment (Ewert and Baker, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It might be expected, for example, that younger, more educated land managers will be more likely to adopt sustainable practices. However, research examining the relationship between socio-demographic variables and proenvironmental attitudes and behaviour has shown conflicting results (Tarrant and Cordell, 1997) and, in general, demographic variables have been found to explain only a small amount of the variance (Wall, 1995). Consistent with this, Cary et al (2001) concluded that there was a weak or non-existent relationship between age and education and adoption of agricultural best practice.…”
Section: Introductionmentioning
confidence: 99%